The Right to Education Amidst the Palestine-Israel Conflict: A Human Rights Perspective - Cintya Nabilla Asrori; Fadhila Muthi’ah Ramadhani; Marsya Azamatul Amalya; Nazwa Difa Nur Atikasari; Salma Masrur (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
The protracted conflict between Israel and Palestine, rooted in historical and geopolitical tensions since the Balfour Declaration of 1917, has resulted in widespread human rights violations, particularly impacting the right to education. This article examines how the ongoing conflict has obstructed access to basic human rights for Palestinians, with a focus on the education sector. Utilizing a qualitative approach through literature review, the study analyzes the impact of military aggression, occupation policies, and systemic restrictions imposed by Israel on Palestinian educational infrastructure, curriculum, and students. The findings reveal significant violations, including school demolitions, curriculum control, displacement of educators and students, and psychological trauma experienced by children. Despite the involvement of international legal instruments and humanitarian organizations such as the UN, ICC, and UNICEF, efforts remain insufficient due to political obstacles and enforcement limitations. The study underscores the urgent need for stronger international accountability and the protection of educational rights in conflict zones, emphasizing that education is not only a fundamental human right but a key to peace, development, and the preservation of cultural identity.